Effects of substrate concentration and agitation rate on butanol production from palm oil mill effluent using clostridium acetobutylicum - Nur Hidayah, Maslam (2010)
This study is mainly focusing on butanol production from palm oil mill effluent (POME) by anaerobic fermentation using Clostridium acetobutylicum. Despite that untreated POME could bring severe effects to environment, POME also can be used as the main substrate due to abundant supply and it potentiality to be utilised by saccharolytic clostridia in butanol fermentation. Reinforced Clostridia Medium (RCM) was functioned as control medium. This study was also to investigate the growth profile rate and the consumption of glucose by C. acetobutylicum during fermentation for 72 hour at 37°C. Fermentation was carried out in 250 mL Schott bottle at a working volume of 150 mL. Other parameters were kept constant at pH 5.8 for POME, pH 6.8 for RCM and 10% inoculum. The effects of substrate concentration and agitation rate in producing butanol were studied. Substrate concentrations used were 70%, 80% and 90% while for agitation rates were 0 rpm, 100 rpm, 175 rpm and 250 rpm. Butanol produced from the fermentation was analyzed using gas chromatography equipped with flame ionization detector (GC-FID). Growth profile rate of C. acetobutylicum in POME and RCM were measured using UV-Vis spectrophotometer. Glucose concentration was measured from the calculation of the amount of glucose consumed by dinitrosalicylic acid (DNS) method which monitored using UV-Vis spectrophotometer. This experiment were started by clostridia cultivation and then followed by fermentation medium preparation, inoculum preparation, fermentation process for 72 hours and fermentation product analysis. The highest butanol yield in POME was 0.3485 g/L at 70% concentration and 175 rpm while maximum butanol production was produced in 90% RCM at 175 rpm which was 0.5034 g/L. In conclusion, lots of hard work and precaution steps need to be taken in order to make sure higher butanol can be produced at theoretically substrate concentration which is 90% and agitation rate at 200 rpm.